Paradigm Shift in the Management of the Atrophic Posterior Maxilla - Rabah Nedir; Nathalie Nurdin; Paul Khoury; Marc El Hage; Semaan Abi Najm; Mark Bischof (Hindawi Limited, 2014)
When the posterior maxilla is atrophic, the reference standard of care would be to perform sinus augmentation with an autologous bone graft through the lateral approach and delayed implant placement. However, placement of short implants with the osteotome sinus floor elevation technique and without graft can be proposed for an efficient treatment of clinical cases with a maxillary residual bone height of 4 to 8 mm. The use of grafting material is recommended only when the residual bone height is ≤4 mm. Indications of the lateral sinus floor elevation are limited to cases with a residual bone height ≤ 2 mm and fused corticals, uncompleted healing of the edentulous site, and absence of flat cortical bone crest or when the patient wishes to wear a removable prosthesis during the healing period. The presented case report illustrates osteotome sinus floor elevation with and without grafting and simultaneous implant placement in extreme conditions: atrophic maxilla, short implant placement, reduced healing time, and single crown rehabilitation. After 6 years, all placed implants were functional with an endosinus bone gain.